Book Reviews - Guillaume, Alfred (The Muslim world, 1957)
Book Reviews in This Article: The Koran Interpreted. By Arthur J. Arberry. Averroes' Commentary on Plato's Republic. Edited with an introduction, translation and notes by E. I. J. Rosenthal. The Concept of Constitutional Law in Islam. By Dr. Rahimuddin Kemat. Islamic Law and Constitution. By Syed Abul Ālā Maudoodi. Kuwait and her Neighbours. By H. R. P. Dickson. Anctent and Modern Man in Southwestern Asia. By Henry Field.